Statistical analysis of dose-volume profiles and its implication for radiation therapy planning in prostate carcinoma - Vanasek, Jaroslav; Odrazka, Karel; Dolezel, Martin; Kolarova, Iveta; Jarkovsky, Jiri; Pavlik, Tomas; Hlavka, Ales; Dusek, Ladislav (International journal of radiation oncology, biology, physics, 2013)
PURPOSE: The study aimed to analyze the dose-volume profiles of 3-dimensional radiation therapy (3D-CRT) and intensity modulated RT (IMRT) in the treatment of prostate carcinoma and to specify the profiles responsible for the development of gastrointestinal (GI) toxicity. METHODS AND MATERIALS: In the period 1997 to 2007, 483 patients with prostate carcinoma in stage T1-3 N0 (pN0) M0 were treated with definitive RT. Two groups of patients were defined for the analysis: the 3D-CRT group (n=305 patients) and the IMRT group (n=178 patients). In the entire cohort of 483 patients, the median follow-up time reached 4.4 years (range, 2.0-11.7 years). The cumulative absolute and relative volumes of irradiated rectum exposed to a given dose (area under the dose-volume curve, AUC) were estimated. The receiver operating characteristic analysis was then used to search for the optimal dose and volume cutoff points with the potential to distinguish patients with enhanced or escalated toxicity. RESULTS: Despite the application of high doses (78-82 Gy) in the IMRT group, GI toxicity was lower in that group than in the group treated by 3D-CRT with prescribed doses of 70 to 74 Gy. Both RT methods showed specific rectal dose-volume distribution curves. The total AUC values for IMRT were significantly lower than those for 3D-CRT. Furthermore, IMRT significantly decreased the rectal volume receiving low to intermediate radiation doses in comparison with 3D-CRT; specific cutoff limits predictable for the level of GI toxicity are presented and defined in our work. CONCLUSIONS: Total area under the dose-volume profiles and specific cutoff points in low and intermediate dose levels have significant predictive potential toward the RT GI toxicity. In treatment planning, it seems that it is valuable to take into consideration the entire dose-volume primary distribution.
Keywords: konformní radioterapie; radioterapie s modulovanou intenzitou; Male; Rectum; ROC Curve; Radiotherapy, Conformal; následné studie; celková dávka radioterapie; Radiotherapy, Intensity-Modulated; Gastrointestinal Tract; Prostatic Neoplasms; mužské pohlaví; rektum; radiační poranění; Follow-Up Studies; Radiotherapy Dosage; plocha pod křivkou; Radiation Injuries; lidé; adenokarcinom; Humans; nádory prostaty; Area Under Curve; gastrointestinální trakt; plánování radioterapie pomocí počítače; Adenocarcinoma; ROC křivka; Radiotherapy Planning, Computer-Assisted